Android-Based Learning Media Design with Contextual Learning to Develop Problem-Solving Skills - Ahmad Yani; Iwit Prihatin; Hodiyanto Hodiyanto; Sumiati Sumiati (Didaktik Matematika, 2021)
This study objective is to show that android-based learning media design with contextual learning is valid, practical, and effective in developing mathematical problem solving skills. The research method used is Research and Devolopment. Its design in this study is 4-D development model consisting of 4 development stages: define, design, develop, and desseminate. The subjects of this study consisted of development subjects (validators) and field trial subjects (a private senior high school in Pontianak, Indonesia). Data collection tools used were validation sheets, questionnaires and mathematical problem solving skill tests. The data analysis technique used descriptive statistics. This study showed that android-based media with contextual learning content was valid, practical and effective in developing mathematical problem-solving skills. In addition, Android-based learning media with contextual learning content could be used as an alternative in learning during Covid 19.